Post-depositional forcing of magnetic susceptibility variations at Kurtak section, Siberia - Chen, Jiasheng; Liu, Xiuming; Kravchinsky, Vadim A.; Lü, Bin; Chen, Qü (Quaternary International, 2016)
Magnetic susceptibility (MS) of aeolian deposits on the Chinese Loess Plateau is high in paleosol and low in loess. The MS of paleosols is mainly enhanced by ferromagnetic minerals formed during post-depositional soil development. In central Alaska, aeolian deposits, MS is high in loess and low in paleosol. The wind vigor model has been proposed to interpret such MS enhancement for the central Alaskan loess. This model suggests that the MS variations are determined by pre-depositional wind strength. The wind vigor model has been introduced to the Siberian Kurtak section where MS is also high in loess and low in paleosol. Additionally to the wind vigor model, low MS in paleosols could be triggered by post-depositional soil development and gleying when the pedogenesis and gleying transforms the ferromagnetic minerals to weak and non-magnetic minerals. In our study of the most continuous Kurtak section in western Siberia, we found that paleosols have substantially more ferruginous mottles due to water-saturated conditions. Magnetic analysis demonstrates that paleosols contain greater content of hard magnetic minerals compared to the loess. Temperature analysis of the MS in the ferruginous mottles shows that magnetic susceptibility increases 37 times after heating and cooling; half of the MS enhancements are contributed due to the heating in between 600 and 700 °C, being caused by the decomposition of non-magnetic chlorite. This suggests that pedogenesis and gleying at the Kurtak section produces weak and non-magnetic minerals in water-saturated anaerobic conditions, which deplete the MS in paleosols after deposition of loess.